Competition between Halogen, Hydrogen and Dihydrogen Bonding in Brominated Carboranes. Issue 21 (22nd September 2016) - Fanfrlík, Jindřich; Holub, Josef; Růžičková, Zdeňka; Řezáč, Jan; Lane, Paul D.; Wann, Derek A.; Hnyk, Drahomír; Růžička, Aleš; Hobza, Pavel
Abstract: Halogen bonds are a subset of noncovalent interactions with rapidly expanding applications in materials and medicinal chemistry. While halogen bonding is well known in organic compounds, it is new in the field of boron cluster chemistry. We have synthesized and crystallized carboranes containing Br atoms in two different positions, namely, bound to C‐ and B‐vertices. The Br atoms bound to the C‐vertices have been found to form halogen bonds in the crystal structures. In contrast, Br atoms bound to B‐vertices formed hydrogen bonds. Quantum chemical calculations have revealed that halogen bonding in carboranes can be much stronger than in organic architectures. These findings open new possibilities for applications of carboranes, both in materials and medicinal chemistry. Abstract : Substituted carboranes can contain Br atoms in two positions, that is, bound to C‐ or to B‐vertices. When Br atoms are bound to C‐vertices, C−Br⋅⋅⋅H−B halogen bonds can be formed in the crystal structure. This is in contrast to Br atoms bound to B‐vertices, where B−Br⋅⋅⋅H−C hydrogen bonds are observed.